The effect of black tea and water temperature on the disintegration of gelatine and HPMC capsules, tested with the paddle device, GastroDuo and in vivo pharmacokinetics: Much ado about little - Dorota Sarwinska; Mathilde Leyh; Constantin Foja; Theodora Tzakri; Philipp Schick; Felix Morof; Julius Krause; James Mann; Richard Barker; Mladen Vassilev Tzvetkov; Werner Weitschies; Michael Grimm (International Journal of Pharmaceutics: X)
Fluid co-administered with oral medication directly affects its behaviour. Often, people use fluids other than water when taking their medications. Capsules (mainly gelatine- and HPMC-based) are widely used solid oral dosage forms. The presented study aimed to investigate the behaviour of gelatine and HPMC capsules in several fluids in vitro and in vivo. The second aim was to assess the influence of administered fluids on the gastric emptying. The third aim was to assess the usability and predictive power of different in vitro methods for drug analysis and compare them with in vivo data. For in vitro studies, two systems with different complexities were used: the compendial USP 2 apparatus and the GastroDuo biorelevant model. In both systems, 25 mL of SGF and 240 mL of tested fluid were used. To obtain the in vivo data, a clinical study with 12 young and healthy volunteers was performed. In this study, the salivary tracer technique, which utilises caffeine kinetics as a marker of a dosage form behaviour in the GIT, was used. In vitro, the temperature strongly affected the opening times of gelatine capsules (rapid opening in warm media and slower in cold). In vivo, the opening time of gelatine capsules in warm black tea was slightly delayed in comparison to warm water. The differences in opening times between warm and cold water and warm black tea and cold water were significant. In USP 2 Apparatus, HPMC capsules were more sensitive to the tested media than in the biorelevant GastroDuo model. There were no significant differences in the opening times of HPMC capsules in vivo. Gastric emptying of warm water, cold water or warm black tea was not affected, suggesting that the altered in vivo absorption kinetics was caused by the in vivo behaviour of the capsules, depending on their properties and not by changes in the gastric emptying of the co-administered fluids. The presented study allows a better understanding of gelatine and HPMC capsules behaviour in vitro and in vivo administered with different fluids. Moreover, it demonstrated the relevance of in vivo data as well as the limitations of in vitro tools.